Komunikasi Lintas Agama Dalam Mempertahankan Kerukunan di Rumah Ibadah Puja Mandala Bali - Ida Selviana masruroh; Mochamad Aris Yusuf (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
The rise of cases of inter-religious harmony conflicts caused by biased interactions and misunderstandings in communication has sparked serious problems. So, communication should be done in an empathetic and tolerant way. The purpose of this article is to answer concerns about how empathic communication can maintain harmony in the Puja Mandala Worship Complex, Bali, as well as what efforts can strengthen harmony between religious adherents at Puja Mandala, Bali. Data collection was achieved through observation, in-depth interviews, and documentation which will be presented through qualitative research methods. The results obtained, that the negotiation of good relations can be through: interpersonal communication, group communication and mass communication. While efforts to maintain harmony can be seen from; construction of places of worship, foreign aid, celebration of religious holidays and broadcasting of religion. This will extinguish the conflict to the national level.